Solution to the Selection of Cross-Border Shippers (SCBS) Problem - Krishnasamy, Ganesh; Kulkarni, Anand Jayant; Abraham, Ajith (Cohort Intelligence: A Socio-inspired Optimization Method, 2017)
In this chapter, we demonstrate the ability of Cohort Intelligence (CI) methodology to solve problem of optimal selection of cross-border shippers and cargo assignments (Kulkarni et al. in European Journal of Operational Research, 2015, [1]). The problem includes various constraints related to due dates, processing times, fund availability, and shippers’ compliance. We formulate and solve the multi-period instance of this problem as well. The performance of the CI method is compared to that of Integer Programming (IP) solution obtained using CPLEX and to specifically developed multi-random-start local search (MRSLS) method.